2016
DOI: 10.15171/ijoem.2016.612
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Functions, Oxidative Stress and DNA Damage in Workers of a Copper Processing Industry

Abstract: The observed DNA damage would be due to increased oxidative stress resulting from excessive exposure to copper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Similar findings were obtained by De Olivera et al (2011). A recent study on copper processing workers revealed DNA damage quantified by comet assay along with decreased antioxidant power of plasma and increased propensity for oxidative stress (Kumar et al, 2016). Several other studies also found significant positive associations between exposure to metals, oxidative stress parameters and primary DNA damage detected in comet assay (Kobal et al, 2004, Rohrdanz and Kahl, 2005and Pease et al, 2016.…”
Section: Discussionmentioning
confidence: 92%
“…Similar findings were obtained by De Olivera et al (2011). A recent study on copper processing workers revealed DNA damage quantified by comet assay along with decreased antioxidant power of plasma and increased propensity for oxidative stress (Kumar et al, 2016). Several other studies also found significant positive associations between exposure to metals, oxidative stress parameters and primary DNA damage detected in comet assay (Kobal et al, 2004, Rohrdanz and Kahl, 2005and Pease et al, 2016.…”
Section: Discussionmentioning
confidence: 92%
“…Earlier studies showed that exposure to pollutants containing Cu, a major component exclusively detected in ABS emissions ( Figure 1 ), can cause oxidative stress and perturb major amino acids metabolisms including tryptophan [ 45 ], lysine [ 46 ], asparagine, glutamine, methionine, and cysteine [ 47 ], and arginine and proline metabolism [ 46 ]. Additionally, exposure to Cu can induce cytotoxicity [ 48 , 49 , 50 , 51 ], and cause mitochondrial dysfunction [ 48 ], which has shown to be associated with compromised lung function [ 52 ] and many other health issues [ 53 , 54 ]. Amino acid metabolism has a central regulatory function in regulating mitochondrial homeostasis, nucleotides biosynthesis, and antioxidant responses [ 41 , 42 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies also demonstrated that in vivo exposure to the thermo-oxidative degradation of ABS caused a decrease in tissue GSH level [ 87 , 88 ]. Furthermore, exposure to pollution containing Cu can also lead to GSH oxidation and depletion [ 51 , 89 ] and elevation of pro-inflammatory cytokines [ 48 , 50 , 90 ], and cause pulmonary inflammation and hypertension [ 91 ], resulting in serious respiratory diseases including COPD and pneumonia mortality [ 92 ]. Dysregulated cellular redox homeostasis is often associated with increased levels of cytokines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although methylation was still not related to human Cu occupational exposure, in addition to its genomic toxicity, Cu can alter histone acetylation and histone deacetylase activity [ 73 ]. Excessive exposure to Cu in a processing industry leads to increased DNA damage and several parameters of oxidative stress, along with alterations in pulmonary function parameters [ 74 ]. In fact, oxidative stress may facilitate tumorigenesis by dysregulating cellular antioxidants, disrupting cell growth and proliferation [ 75 ], which are enabled by telomere balance in length, structure, and proper function [ 76 ].…”
Section: Discussionmentioning
confidence: 99%